2019
DOI: 10.3329/jninb.v5i2.43015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ICU Outcomes between Intravenous Immunoglobulin and Plasma Exchange in Treatment of Mechanically Ventilated Patients with GuillainBarré Syndrome in a Neuro-Intensive Care Unit in a Govt. Hospital of Bangladesh: A Observational Cohort Study

Abstract: Background: The management of Guillain-Barré Syndrome is very crucial for the outcome of the patient. Objective: The aim of the study was to compare efficacy of IvIg(Intravenous Immunoglobulin) versus PE(Plasmaexchange) in treatment of mechanically ventilation adults with GBS in neuro-intensive care unit of Bangladesh. Methodology: Thiswas a prospective, observationalcohort study, in a Neuro-ICU from 2017 to 2018. We included all patients with GBS who required mechanical ventilation (MV). We define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Moreover, we found that the time until discontinuation from MV was similar in both IVIG and PE groups. The finding is contradicted by Mallick and colleagues, who reported that the patients treated with IVIG were weaned from MV earlier than the patients treated with PE ( p = 0.002) [ 26 ]. However, the results of that study cannot be used to guide clinical treatment with IVIG since the study included a small number of patients and was designed as an observational study with poor methodological quality.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, we found that the time until discontinuation from MV was similar in both IVIG and PE groups. The finding is contradicted by Mallick and colleagues, who reported that the patients treated with IVIG were weaned from MV earlier than the patients treated with PE ( p = 0.002) [ 26 ]. However, the results of that study cannot be used to guide clinical treatment with IVIG since the study included a small number of patients and was designed as an observational study with poor methodological quality.…”
Section: Discussionmentioning
confidence: 92%
“…Our analysis did not demonstrate any significant difference in complication rates between patients receiving IVIG and PE. However, one study which led to significant differences in the analysis was eliminated because we could not tell whether these complications were a result of the mechanical ventilation or the treatments used for GBS [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of GBS varies from spontaneous recovery to wheelchair dependency to death. Case fatality rate and poor outcome is lower in high-income countries in comparison to low-income country [8]. But there were few studies regarding in-hospital outcome and predictors of poor in-hospital outcome.…”
Section: Introductionmentioning
confidence: 96%
“…Mallick et al and Saad et al reported that patients treated with PE had lowered hospitalization costs due to far shorter ICU stays and shorter periods of MV than patients treated with IVIG[18,16].Beydoun et al …”
mentioning
confidence: 99%